A Workshop on Writing a Systematic Literature Review Using Artificial Intelligence (AI)-Based Tools - Emilius German; Rijal Hakiki; Ani Pujiastuti; Disa Evawani Lestari; Risa Fitria (President University, 2024)
To generate meaningful research, lecturers and investigators have to identify strong, innovative research ideas. However, they often have difficulty with digesting a large number of relevant studies when conducting literature review. The workshop on